Benefits of vegetation for mitigating wave impacts on vertical seawalls. (15th April 2022) - Rosenberger, Daniel; Marsooli, Reza
Abstract: This study quantifies the benefits of vegetation for reducing wave loads on seawalls and the probability of failure due to sliding and overturning. A computational fluid dynamic model is used to quantify wave forces and moments on a laboratory-scale vertical seawall in the presence and absence of vegetation. The model is first calibrated using existing laboratory measurements and then implemented to simulate wave impacts under 200 various wave scenarios. The simulated forces are analyzed to calculate the sliding force and overturning moment and quantify the benefit of vegetation for reducing the seawall failure incidents and increasing the factor of safety. Under the laboratory-scale conditions considered in this study, vegetation causes a reduction of up to 89 percent in the wave force, leading to a substantial decrease in sliding and overturning failure scenarios and increase in the scenarios with acceptable factors of safety. It is found that a smaller seawall combined with vegetation results in an overturning and sliding performance, in terms of failure and factor of safety, similar to the performance of a larger seawall without vegetation. The results suggest that vegetation has a potential to protect coastal structures and allow engineers to design efficient hybrid nature-based and engineering defenses. Highlights: Vegetation reduces impulsive wave forces on a vertical seawall Vegetation increases the seawall reliability against sliding and overturning failures A smaller seawall could be designed if the seawall is combined with vegetation